Evolution of organogenesis and the origin of altriciality in mammals. Issue 4 (July 2016) - Werneburg, Ingmar; Laurin, Michel; Koyabu, Daisuke; Sánchez‐Villagra, Marcelo R.
SUMMARY: Mammals feature not only great phenotypic disparity, but also diverse growth and life history patterns, especially in maturity level at birth, ranging from altriciality to precocity. Gestation length, morphology at birth, and other markers of life history are fundamental to our understanding of mammalian evolution. Based on the first synthesis of embryological data and the study of new ontogenetic series, we reconstructed estimates of the ancestral chronology of organogenesis and life‐history modes in placental mammals. We found that the ancestor of marsupial and placental mammals was placental‐like at birth but had a long, marsupial‐like infancy. We hypothesize that mammalian viviparity might have evolved in association with the extension of growth after birth, enabled through lactation, and that mammalian altriciality is inherited from the earliest amniotes. The precocial lifestyle of extant sauropsids and that of many placental mammals were acquired secondarily. We base our conclusions on the best estimates and provide a comprehensive discussion on the methods used and the limitations of our dataset. We provide the most comprehensive embryological dataset ever published, "rescue" old literature sources, and apply available methods and illustrate thus an approach on how to investigate comparatively organogenesis in macroevolution.